2016
DOI: 10.1021/acs.analchem.6b02900
|View full text |Cite
|
Sign up to set email alerts
|

Accurate, Direct, and High-Throughput Analyses of a Broad Spectrum of Endogenously Generated DNA Base Modifications with Isotope-Dilution Two-Dimensional Ultraperformance Liquid Chromatography with Tandem Mass Spectrometry: Possible Clinical Implication

Abstract: Our hereby presented methodology is suitable for reliable assessment of the most common unavoidable DNA modifications which arise as a product of fundamental metabolic processes. 8-Oxoguanine, one of the oxidatively modified DNA bases, is a typical biomarker of oxidative stress. A noncanonical base, uracil, may be also present in small quantities in DNA. A set of ten-eleven translocation (TET) proteins are involved in oxidation of 5-methylcytosine to 5-hydroxymethylcytosine which can be further oxidized to 5-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 43 publications
2
58
0
Order By: Relevance
“…This proposed epigenetic regulation by 8-oxoGua would be in contrast to the role of 5-mCyt, which is responsible for transcription suppression. Interestingly, in our recently published study, we demonstrated a negative correlation between background levels of 8-oxoGua and 5-mCyt in DNA [27]. The mechanisms that underly site-specific DNA modifications, chromatin changes, and transcription, are highly complex and may depend on numerous factors, such as sequence context, tissue differences or/and specific proteins assembly, to name a few [48,50].…”
Section: Potential Regulatory Role Of 8-oxoguamentioning
confidence: 71%
See 1 more Smart Citation
“…This proposed epigenetic regulation by 8-oxoGua would be in contrast to the role of 5-mCyt, which is responsible for transcription suppression. Interestingly, in our recently published study, we demonstrated a negative correlation between background levels of 8-oxoGua and 5-mCyt in DNA [27]. The mechanisms that underly site-specific DNA modifications, chromatin changes, and transcription, are highly complex and may depend on numerous factors, such as sequence context, tissue differences or/and specific proteins assembly, to name a few [48,50].…”
Section: Potential Regulatory Role Of 8-oxoguamentioning
confidence: 71%
“…Recently, using LC-MS/MS-based methodology and after exclusion of the most likely factors responsible for potential artifactual formation of Ura in DNA (e.g. contamination of reagents with deaminases), the baseline level of Ura was estimated to be in the range of 0.056 to 4.03 dU/10 6 deoxuynucleosides (dN) in cultured cells lines [24,25], 1 to 9.6 dU/10 6 dN in human leukocytes [26], 11.41 dU/10 6 dN in human colorectal cancer tissue and 12.17 dU/10 6 dN normal colon tissue from the tumour's margin [27].…”
Section: The Background Level Of Ura In Dnamentioning
confidence: 99%
“…1B). Sensitive chromatographic methods coupled with electrospray tandem mass spectrometry (HPLC-ESI-MS/ MS) [36,38,39], in combination with the use of stable isotope-labeled standards [18,40,41], enabled researchers to determine global levels of cytosine-related epigenetic bases in stem cells and in various mammalian tissues. Cytosine modifications can also be detected based on DNA digestion by modification-sensitive restriction enzymes.…”
Section: Epigenetic Modifications Of Cytosinementioning
confidence: 99%
“…Leukocytes were isolated from heparinized blood samples with Histopaque 1119 (Sigma, United Kingdom) solution, according to the manufacturer's instruction, and stored at -80°C until the analysis. Isolation of leukocyte DNA and its hydrolysis were carried out as previously described [27], but the cell pellet was immediately dispersed in ice-cold lysing buffer B, without homogenization and washing steps. Procedures used for the determination of 5-methyl-2'-deoxycytidine (5-mdC), 5-(hydroxymethyl)-2'-deoxycytidine (5-hmdC), 5-formyl-2'deoxycytidine (5-fdC), 5-carboxy-2'deoxycytidine (5-cadC), 5-(hydroxymethyl)-2'-deoxyuridine (5-hmdU) and 8-oxodG by 2D-UPLC-MS/MS have been described elsewhere [27].…”
Section: Isolation Of Dna and Determination Of Epigenetic Modificatiomentioning
confidence: 99%
“…Due to very low level of these modifications in mammalian genome (approximately 3-4 orders of magnitude lower than 5-hmCyt content), their accurate determination is highly challenging. In this study, we used our recently developed rapid, highly-sensitive and highly-specific isotope-dilution automated online two-dimensional ultra-performance liquid chromatography with tandem mass spectrometry (2D-UPLC-MS/MS) [26,27] to analyze global methylation and the levels of all the abovementioned TET-mediated oxidation products of 5-mCyt and thymine: 5-hmCyt, 5-fCyt, 5-caCyt and 5-hmUra. Moreover, we determined leukocyte content of the best characterized marker of oxidatively modified DNA, 8-oxo-7,8-dihydro-2'-deoxyguanosine (8-oxodG), as well as the expression of TETs mRNA, and plasma concentrations of ascorbate and retinol.…”
mentioning
confidence: 99%